Acute Schistosomiasis in Brazilian Traveler: The Importance of Tourism in The Epidemiology of Neglected Parasitic Diseases - Diego Averaldo Guiguet Leal; Regina Maura Bueno Franco; Maria Francisca Neves; Luciana Franceschi Simões; Letícia Aparecida Duart Bastos; Silmara Marques Allegretti; Eliana Maria Zanotti-Magalhães; Luiz Augusto Magalhães (Case Reports in Infectious Diseases)
Parasitic infectious diseases acquired in tourist areas may pose a challenge to physicians and to travel medicine practitioners. Acute schistosomiasis may be seen in returning travelers and migrants after primary infection. This form of schistosomiasis is frequently misdiagnosed due to its temporal delay and its nonspecific presentation and might occur even in countries where the disease is endemic, such as in Brazil. The patient developed the acute phase of schistosomiasis with severe clinical manifestations. The quantitative analysis revealed the presence of 240 eggs per gram of stool. The treatment was administered with oxamniquine, and the control of cure of the patient was monitored and was favorable. The present paper aims to emphasize the importance of a detailed clinical history including information regarding travel history.